The one-year incidence of mental disorders among UP Manila College freshmen study on family dysfunction and other variables - Ruiz, Roberto L.
Venomous Conus textile is one of the most abudant Conidae found in Philippine waters. The toxic manifestation of C. textile venom was studied in relation to its hematoxic property. Toxicity tests on mice showed that the venom is lethal only when injected intracisternally. The toxic principle has been demonstrated to be sensitive to pronase and to be non-dialyzable. These plus the high protein content of the venom suggest that the toxic factor could be a protein. Disc gel electrophoresis of the venom protein indicated the presence of a few major proteins with molecular weights of 10,000 to 100,000 daltons. Using casein as a substrate, the proteolytic activity of the venom was studied and measured in terms of tyrosine liberated per minute per mg protein. Different enzyme parameters such as time, concentration, temperature and pH were tested. A preliminary attempt was made to relate hemolytic activity to proteolytic activity using the technique of gel filtration. Results indicated three hemolytic and two proteolytic peaks but only one hemolytic peak coincided with a proteolytic peak.